William Carey and the Indian renaissance - Dewanji, Malay; Uiliy ama Ker i S|t a|di ey a|n|da Ris arca Se|n|t ara.; Christian Institute for the Study of Religion and Society; I.S.P.C.K. (Organization) (Delhi : Published for William Carey Study and Research Centre & Christian Institute for the Study of Religion and Society by ISPCK, 1996)
Brief biography of William Carey, 1761-1834, Baptist missionary and his efforts in the development of Bengali language, literature, and education.
Keywords: Carey, William, -- 1761-1834.; Missionaries -- England -- Biography; Baptists -- England -- Biography; Missionaries -- India -- Biography; Baptists -- India -- Biography; Bengali philology -- History